Aerosol-Assisted Assembly of Mesoporous Carbon Spheres With Fast and Stable K-ion Storage - Guo, Yu; Li, Jiahui; Wang, Hairui; Chang, Limin; Rui, Binglong; Lin, Li; Xu, Tianhao; Nie, Ping (Frontiers in Chemistry, 2020)
Cost effective anode material with rational design is of significance for rechargeable potassium ion batteries (KIBs). Graphite anode currently still suffers unfavorable rate capability and moderate cycling stability. In this work, we report a mesoporous carbon sphere with rich porous structure as an anode material for KIBs with the assistance of an aerosol spray technology. The as-developed carbon spheres exhibit a well-defined spherical structure with favorable surface area of 1106.32 m2 g−1. Furthermore, the effect of different electrolytes on the electrochemical performance of the carbon anode has been investigated systematically. As expected, the carbon material shows excellent potassium storage performance in terms of improved specific capacity of 188.2 mAh g−1, rate capability and prolonged cyclability with a high capacity of 105.3 mAh g−1 after 500 cycles at a rate of 100 mA g−1 toward potassium storage in KFSI based carbonate electrolyte.